Infiltrating monocytes in liver injury and repair - Brempelis, Katherine J (Clin Transl Immunology, 2016)
Noninfectious liver injury causes many acute and chronic liver diseases around the globe, and particularly in developed nations. Bone marrow-derived monocytes infiltrate the damaged liver tissue and are a critical component of the innate immune response that may drive injury resolution or host death in the short term or chronic inflammation, fibrosis and hepatocellular carcinoma in the long term. Monocytes often play dual roles in liver injury—both perpetuating inflammation and promoting resolution of inflammation and fibrosis. Thus, we will address the role that monocytes play in different experimental forms of noninfectious liver injury; considering in particular the importance of the transition from inflammatory Ly6C(hi) monocytes to pro-resolution Ly6C(lo) monocyte-derived macrophages and the consequences of this transition for disease progression and resolution.